2002
DOI: 10.1016/s0304-8853(02)00550-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal process and nonlinear magneto-impedance in Cu/NiFe and Nb/NiFe composite wires

Abstract: The magnetization reversal of Cu/NiFe and Nb/NiFe composite wires carrying AC current is studied. The frequency spectrum of a voltage induced in a pick-up coil wound around the wire is analyzed. The frequency spectrum is shown to consist of even harmonics within a wide range of AC current amplitudes and longitudinal DC magnetic fields. The strong dependencies of the harmonic amplitudes on the DC field are found. The results obtained may be of importance for the design of weak magnetic field sensors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…It has also been reported that Cu wire plated with a 1-4 m thick NiFe magnetic layer shows large GMI effect. The magnitude of the GMI effect varies between 40% and 600% depending on the Cu wire diameter, electrodeposition parameters such as the pH of the solution, current density, plating time and composition of the solution [10,12,[13][14][15][16][17]. Therefore in this study, the effect of the NiFe film thickness plated on a Cu wire was investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that Cu wire plated with a 1-4 m thick NiFe magnetic layer shows large GMI effect. The magnitude of the GMI effect varies between 40% and 600% depending on the Cu wire diameter, electrodeposition parameters such as the pH of the solution, current density, plating time and composition of the solution [10,12,[13][14][15][16][17]. Therefore in this study, the effect of the NiFe film thickness plated on a Cu wire was investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…A significant nonlinear magnetoimpedance effect (NLMI), that is, the variation with magnetic field of the higher harmonic components of the magnetoimpedance signal, has been recently reported for homogeneous and composite wires (conductive wires coated with magnetic layers) [2][3][4][5]. In particular, a clear correlation between the occurrence of the second harmonic (V 2f ) in the magnetoimpedance signal and the existence of an asymmetry in the associated circumferential magnetization process has also been reported [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to the technique developed in [4], we use the second short coil (2 mm), call it external, (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%